How are the Characteristics of Integrated Assessment Instruments to Measure Critical Thinking Skills and Scientific Attitudes of High School Students? - Mir'atul Hasanatin; Eli Rohaeti (Postgraduate, University of Mataram, 2021)
This research aimed to develop an integrated assessment instrument and to study the instrument’s characteristics. This research used 4-D development model of which the stages included defining, designing, developing, and disseminating. The primary product is validated by expert judgment. This research involved 274 mathematics and natural science eleventh-grade students of Senior High Schools in Sleman district, Yogyakarta. The polytomous data generated by the instrument trial was analyzed using the WINSTEPS 3.73 program and the Partial Credit Model 1-Parameter Logistic (PCM 1-PL) approach. Data collecting techniques included interviews, questionnaires, and tests. Data collecting instruments included interview guidelines, a question item validation sheet, and the integrated assessment instrument an essay test. The result of the research shows that the integrated assessment instrument has 0.93 of Aiken validation value. All tryout test items were stated to fit with the PCM 1-PL based on the criteria for the lowest and the highest limit outfit MNSQ 0.5 and 1.5. Item reliability was 0.96 and person reliability was 0.71. The difficulty level of question items was good, because of the range from -1.05 to +1.01 logit. Therefore, the integrated assessment instrument is suitable to be applied to measure the student’s critical thinking skills and scientific attitudes.